The Adequacy of the Teaching Practice Supervision observation instruments for the Post Graduate Diploma Students of Zimbabwe Open University (ZOU): A case study of Midlands Region ZOU - Saiden, Thondhlana (Advances in Social Sciences Research Journal, 2017)
The purpose of the study was to establish the adequacy of the Teaching Practice observation instruments for the Post Graduate Diploma (PGDE) of the ZOU. The instrument was studied in terms of how it addressed before lesson delivery activities, during lesson activities, after lesson activities and personal dimensions. The sample consisted of 16 supervisors and 19 student teachers conveniently sampled. A qualitative research methodology was adopted. The study established that the instruments generally had most issues but mark allocation needed separation, the instruments, could not be attended to objectively in the single lesson of supervision. It was recommended marks should be debunched, a variety of instruments attending to certain areas be used and the supervision time to be increased.